Emotions and fuel poverty: The lived experience of social housing tenants in the United Kingdom. (October 2019) - Longhurst, Noel; Hargreaves, Tom
Abstract: Dominant policy understandings of fuel poverty tend to overlook its lived experience. This results in narrow, technical problem framings that neglect the multiple, inter-related and dynamic factors that shape everyday experiences of energy consumption. Consequently, the concept of energy vulnerability has been used as the basis of recent qualitative work that has begun to recognise the importance of subjective experiences but, to date, emotions have not been central to such analyses. This paper explores a range of emotional engagements with energy vulnerability. The paper draws on new empirical data taken from 16 semi-structured interviews with social housing tenants as well as 10 interviews and a focus group (n=8) with housing association employees. Two broad ways in which emotions shape experiences of energy vulnerability are highlighted. First, how fear, worry and care practices shape patterns of energy use and payment. Second, how care, embarrassment, stigma and trust can facilitate or prevent the receipt of support for energy vulnerable households. Crucially, and for the first time, the paper shows that emotions are not merely a consequence of energy vulnerability but can also contribute to and shape it. The paper concludes with a discussion of the policy and research implications of these findings.